2021
DOI: 10.1038/s41467-021-25769-z
|View full text |Cite
|
Sign up to set email alerts
|

Molecular correlates of response to eribulin and pembrolizumab in hormone receptor-positive metastatic breast cancer

Abstract: Immune checkpoint inhibitors (ICIs) have minimal therapeutic effect in hormone receptor-positive (HR+ ) breast cancer. We present final overall survival (OS) results (n = 88) from a randomized phase 2 trial of eribulin ± pembrolizumab for patients with metastatic HR+ breast cancer, computationally dissect genomic and/or transcriptomic data from pre-treatment tumors (n = 52) for molecular associations with efficacy, and identify cytokine changes differentiating response and ICI-related toxicity (n = 58). Despit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(20 citation statements)
references
References 96 publications
2
18
0
Order By: Relevance
“…Furthermore, in a mixed lymphocyte reaction assay, sintilimab increased interleukin-2 and interferong in a dose-dependent manner, similar to nivolumab; however, sintilimab did not induce cytokine release (8). Gene expression analyses evaluating the association between clinical outcome with sintilimab and a specific immune cell signature revealed that a longer PFS and/or OS was attained in patients who had a higher MHC-II-associated gene expression (10), which has also been previously observed with pembrolizumab and nivolumab (21,22). This potentially implicates antigen presentation pathways, such as MHC-II pathway, in the mechanism of action and a crucial component to attain clinical benefit from sintilimab combination therapy (10).…”
Section: Mechanism Of Action and Class Effect Of Anti-pd-1/pd-l1 Inhi...supporting
confidence: 73%
“…Furthermore, in a mixed lymphocyte reaction assay, sintilimab increased interleukin-2 and interferong in a dose-dependent manner, similar to nivolumab; however, sintilimab did not induce cytokine release (8). Gene expression analyses evaluating the association between clinical outcome with sintilimab and a specific immune cell signature revealed that a longer PFS and/or OS was attained in patients who had a higher MHC-II-associated gene expression (10), which has also been previously observed with pembrolizumab and nivolumab (21,22). This potentially implicates antigen presentation pathways, such as MHC-II pathway, in the mechanism of action and a crucial component to attain clinical benefit from sintilimab combination therapy (10).…”
Section: Mechanism Of Action and Class Effect Of Anti-pd-1/pd-l1 Inhi...supporting
confidence: 73%
“…An apparent dysfunction in ovarian steroidogenesis has been shown to be associated with polycystic ovarian syndrome and plays a crucial role in its prognosis [ 47 , 48 ]. Researchers found that approximately 70% of invasive breast cancers have some degree of independence from the estrogen hormone for cell proliferation and growth [ 49 ], and Keenan et al found that estrogen signaling was independently associated with resistance in hormone-positive breast cancer [ 50 , 51 ]. These studies suggest that the dysfunction pathways identified by our study are partly associated with the development and progression of tumors.…”
Section: Resultsmentioning
confidence: 99%
“…In the TAPUR and NIMBUS studies, a subset of patients with MBC and high tTMB across subtypes were durable responders (31,53). However, in other non-biomarker selected populations, there has been no improvement in outcomes when adding ICI to chemotherapy (54). For this reason, evaluating the potential of incorporating ICI for HR+/HER2-negative patients with high bTMB, either as monotherapy or in combination, is needed.…”
Section: Discussionmentioning
confidence: 99%